2013
DOI: 10.1002/path.4192
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of CSF family cytokines in macrophage infiltration and activation in glioma progression and injury response

Abstract: Gliomas attract brain-resident (microglia) and peripheral macrophages and reprogram these cells into immunosuppressive, pro-invasive cells. M-CSF (macrophage colony-stimulating factor, encoded by the CSF1 gene) has been implicated in the control of recruitment and polarization of macrophages in several cancers. We found that murine GL261 glioma cells overexpress GM-CSF (granulocyte-macrophage colony-stimulating factor encoded by the CSF2 gene) but not M-CSF when compared to normal astrocytes. Knockdown of GM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(126 citation statements)
references
References 56 publications
2
118
1
2
Order By: Relevance
“…The complexity of GM-CSF biology is evident, because it is implicated in inflammatory conditions, such as rheumatoid arthritis and crescentic GN, 33 but also, as an inducer of M2 markers in microglia/macrophages surrounding glioblastoma tumor cells. 34 Nonhematopoietic cells, such as vascular smooth muscle cells and colon epithelial cells, have been reported to be important sources of GM-CSF, mediating atherogenic monocyte activation 35 and promoting colonic epithelial cell proliferation in colitis, 36 respectively. In addition, GM-CSF has been associated to Th2 immune responses in allergic lung inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of GM-CSF biology is evident, because it is implicated in inflammatory conditions, such as rheumatoid arthritis and crescentic GN, 33 but also, as an inducer of M2 markers in microglia/macrophages surrounding glioblastoma tumor cells. 34 Nonhematopoietic cells, such as vascular smooth muscle cells and colon epithelial cells, have been reported to be important sources of GM-CSF, mediating atherogenic monocyte activation 35 and promoting colonic epithelial cell proliferation in colitis, 36 respectively. In addition, GM-CSF has been associated to Th2 immune responses in allergic lung inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Malgorzata Sielska et al [20] revealed that autocrine GM-CSF had little or no effect on cell viability or the proliferation of glioma cells. There were also conflicting data implicating GM-CSF in the progression of a number of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, TAM prime endothelial cells to sproute as they synthesize and release TNF-α and also other angiogenic molecules which have direct angiogenic effects or promote the secretion of vascular endothelial growth factor from glioma cells [140,101] ( Fig. 3).…”
Section: The Pro-angiogenic Role Of Myeloid Cells In Gliomasmentioning
confidence: 99%